Illness anxiety disorder and perception of disease and distress among medical students in western Saudi Arabia - Ezmeirlly, Heba A. (Saudi Med J, 2019)
OBJECTIVES: To estimate and assess the prevalence and predictors of illness anxiety disorder among Saudi medical students in western Saudi Arabia. METHODS: A cross-sectional study was conducted from November 2017 to March 2018 at King Saud bin Abdulaziz University for Health Sciences, Jeddah, Saudi Arabia. A self-administered questionnaire was applied. The questionnaire is composed of demographic data, the short version of the Health Anxiety Inventory (SHAI), the Medical Student’s Disease (MSD) perception and distress scale and history of a visit to a physician in the past 6 months. RESULTS: Two hundred and seventy-one Saudi medical students participated; 71% were males and 53% were less than 22 years old. The participants represented all academic years, with 54% in their 4th, 5th, and 6th years. Illness anxiety disorder was identified in 17% of the participants. Younger students and those with a history of a physician’s visit within the past 6 months were more likely to have illness anxiety disorder (OR=2.31, 95% CI= 1.16, 4.60; OR=2.46, 95% CI=1.25, 4.84). CONCLUSIONS: The prevalence of illness anxiety disorder among Saudi medical students is comparable to similar recent studies. Student counseling programs highlighting coping techniques, especially during the early study years, should be implemented.